Mengungkap Potensi Fraud Dan Upaya Pencegahannya Di Perusahaan X - Priyo Budi Prakoso; Bambang Haryadi; Oyong Lisa (Universitas Muhammadiyah Malang, 2022)
Any weakness of a control in the company will have the potential for fraud. Those who have more ability to take advantage of this gap will benefit from their actions. Weaknesses of a control, error of recording to incomplete supporting evidence can be the cause of potential fraud. The object of the study is Unit S in Company X. This study provides results that there is still weak control in Unit S, and there are still many recording errors that are not based on fundamental evidence in presenting figures on financial statements. That is, it has the potential to cause fraud in Unit S. fraud which is most worried is the existence of fraud in terms of profit management. Some prevention that can be done is to change or improve the existing control system and complete the supporting evidence in the next period. This research is expected to be a suggestion for companies to be more careful and immediately correct the weaknesses that occur, so that this does not become the cause of potential fraud in the company in the future.